Granice ironii – granice iluzji. O ontologii postaci w „Eugeniuszu Onieginie” Aleksandra Puszkina i Piotra Czajkowskiego - Borkowska-Rychlewska, Alina (Poznańskie Studia Polonistyczne. Seria Literacka, 2022)
The article presents the characteristics of the romantic irony employed in Alexander Pushkin’s digressive poem Eugene Onegin and Pyotr Tchaikovsky’s opera titled alike. The analysis of selected fragments of the libretto which were based on the verses constituting the digressive (rather than storytelling) layer of Pushkin’s work allow one to conclude that the operatic version of Onegin expresses exactly the same kind of romantic irony which was used by the romantic poet. The authors of the libretto achieved something typical of Pushkin’s irony – a flow of the border between illusion and disillusion and an effortless crossing of the dialectic borders of time and space. They did so by multiplying and splitting into layers the “I” of the main character which functions both in the dramatic plane and beyond it, taking over the functions which in Pushkin’s text were performed by the narrator.